Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1365-2184.1994.tb01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in proliferative response and subpopulations of lymphocytes from mice housed in a constant environment

Abstract: A seasonal variation in the proliferative response to mitogens and in the proportion of splenic lymphocyte subpopulations was found in mice housed in a constant environment. The lymphoproliferative responses to T-cell and B-cell mitogens reached maximum values in autumn and summer. Identification of lymphocyte subpopulations by flow cytometry demonstrated that the proportion of T cytotoxic-suppressor (Tcs) lymphocytes was significantly higher in autumn and summer than in spring and winter. However, the proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Planelles et al (35) showed that mice housed in a constant environment had seasonally different lymphoproliferative responses of splenic T and B cells to mitogenic stimuli, and the portion of CD8-positive cytotoxic T lymphocytes in the spleen were maximal in autumn and summer and may be predetermined by an inherent internal biological rhythm. But, how could this light-independent rhythm be generated?…”
Section: Discussionmentioning
confidence: 98%
“…Planelles et al (35) showed that mice housed in a constant environment had seasonally different lymphoproliferative responses of splenic T and B cells to mitogenic stimuli, and the portion of CD8-positive cytotoxic T lymphocytes in the spleen were maximal in autumn and summer and may be predetermined by an inherent internal biological rhythm. But, how could this light-independent rhythm be generated?…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, distinct mechanisms with the same periodicity may uniquely influence seasonal variation in immunity and reproduction, particularly as immunologic circannual rhythms also persist under controlled conditions in domesticated rats and mice (131)(132)(133)(134)(135)(136)(137)(138). Notwithstanding, our documentation that M-SOB effects in chronic human diseases can be modeled in mice will allow for detailed analysis of mechanisms that are associated with M-SOB effects in not only MS, but numerous other human diseases in which M-SOB impacts disease susceptibility during their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…A moderate to high degree of intraand interindividual variation in cell-mediated immune responses has been documented 20,[29][30][31][32][33][34][35] in other species. Analysis of this information suggests that there is a substantial amount of variation in the cell-mediated immune response within and among horses by 24 hours after ID injection of PHA.…”
Section: Discussionmentioning
confidence: 99%